Greenhouse gas emissions from beef grazing systems in semi-arid rangelands of central Argentina - Nieto, Maria Isabel; Barrantes Díaz, Olivia; Privitello, Liliana; Reine Viñales, Ramón (MDPI, 2019)
The livestock sector can be a major contributor to the mitigation of greenhouse gas (GHG) emissions. Within the sector, beef production produces the largest proportion of the livestock sector’s direct emissions. The objective of this study was to assess the on-farm GHG emissions in semi-arid rangelands in Argentina and to identify the relationship between emissions and current farm management practices. A survey recorded detailed information on farm management and characteristics. Assessments of GHG emissions were based on the Intergovernmental Panel on Climate Change (IPCC) Tier 2 protocols. The relationship between farm management and GHG emissions were identified using general linear models. Cluster analysis was used to identify groups of farms that differed from others in emissions and farm characteristics. Emissions per product sold were low on farms that had improved livestock care management, rotational grazing, received technical advice, and had high animal and land productivities. Emissions per hectare of farmland were low on farms that had low stocking rates, a low number of grazing paddocks, little or no land dedicated to improved pastures and forage crops, and low land productivity. Our results suggest that the implementation of realistic, relatively easy-to-adopt farming management practices has considerable potential for mitigating the GHG emissions in the semi-arid rangelands of central Argentina.